Remote sensing technology for disaster mitigation and regional infrastructure planning in urban area: a review - Muhammad Dimyati; Akhmad Fauzy; Anggara Setyabawana Putra (Universitas Ahmad Dahlan, 2019)
A Very high intensity of regional development is ubiquitous in urban areas. Therefore, urban development requires a proper spatial development strategy in many facets, especially social aspect and disaster potential. The essence of social aspect lies in the prevailing norms and local wisdom that have long existed and become the basis of community life. Inducing various effects on infrastructure development, disaster potential has to be considered as well. Disaster mitigation measures can start with the use of continually developing remote sensing technology, which provides a basis for preparing sustainable development planning. The realization of these measures in urban areas demands specific adjustment to the environmental conditions. This study aimed to examine the capacity of remote sensing data to support disaster mitigation and infrastructure planning based on energy conservation in urban areas. The results indicate that remote sensing technology can be an option for sustainable development planning in urban areas.